Development of printer nozzle for extruding synthetic biomaterials using fused deposition modeling process - Sukindar, Nor Aiman (2018)
This research focuses on the development of nozzle specifically for opensource 3D printing for extrusion of synthetic biomaterials. The factors that affect the stability, consistency and accuracy of the extrusion process were investigated by using finite element analysis (FEA) including nozzle die angle, nozzle diameter and liquefier design. From the simulations, it is seen that the die angle and nozzle diameter affect the pressure drop along the liquefier. The pressure drop variation has affected the road width of the printed parts, thus affecting the quality of the finished product. Based on the simulations, the convergent angle for extruding polylactic acid (PLA) and polymethylmethacrylate (PMMA) materials was found in this research at 130o which provides stability and consistency of the extrusion process. For efficient printing process, nozzle diameter of 0.3 mm was found to be the optimum with respect to pressure drop and printing time. The liquefier design plays an important role in maintaining the liquefier chamber’s temperature as constant as possible. The temperature variation has caused the changes in viscosity of the material, thus affecting the quality of the finished parts. Liquefier in cylindrical shape has been identified as the solution in minimizing the problems as it has been proven from the simulations that portray improved temperature distribution. The newly developed nozzle was compared with the original nozzle with respect to dimensional accuracy and mechanical properties and shows that the newly developed nozzle had a better performance in both criteria. By solving the issues related stability, consistency and accuracy of the extrusion process, the scaffold structure was successfully fabricated with compressive strength between 6 MPa to 7 MPa and porosities between 50% and 70% which is the range for trabecular bone. Furthermore, humerus bones was successfully fabricated with controlled porosity.